2014
DOI: 10.1021/jf5038163
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Flavanone Glycosides after Ingestion of Single Doses of Fresh-Squeezed Orange Juice versus Commercially Processed Orange Juice in Healthy Humans

Abstract: Orange juice is a rich source of flavonoids considered beneficial to cardiovascular health in humans. The objective of this study was to analyze the pharmacokinetics of the main flavanone glycosides, hesperidin and narirutin, in humans after the consumption of two styles of orange juice, fresh-squeezed (FOJ) and commercially processed (POJ), differing in their amounts of soluble and insoluble forms of these compounds. Healthy human subjects consumed 11.5 mL/kg body weight of FOJ, and after an interval of 30 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 47 publications
5
41
1
1
Order By: Relevance
“…These conflicting results between in vivo and in vitro examinations may be explained by the metabolism of narirutin in a living body. Pharmacokinetics of narirutin after ingestion of orange juice in healthy humans were reported by Silveria et al [27] . The majority of oral intake-narirutin is considered to reach the colon, and colonic microbiota deglycosylate narirutin to naringenin, that is then absorbed by colonocytes [28] .…”
Section: Discussionmentioning
confidence: 86%
“…These conflicting results between in vivo and in vitro examinations may be explained by the metabolism of narirutin in a living body. Pharmacokinetics of narirutin after ingestion of orange juice in healthy humans were reported by Silveria et al [27] . The majority of oral intake-narirutin is considered to reach the colon, and colonic microbiota deglycosylate narirutin to naringenin, that is then absorbed by colonocytes [28] .…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, an analytical evaluation revealed that the qualitative composition is not changed, but quantitative analysis highlights significant differences [76]. However, the matrix factor is not the most critical.…”
Section: Pharmacokinetic Profile Of Citrus Flavanonesmentioning
confidence: 99%
“…Human intervention studies with hesperidin and food products containing hesperidin such as orange juice, have led to the identification and quantification of hesperidin‐derived metabolites in both plasma and urine . In addition, to elucidate the mechanisms of hesperidin conversion throughout the gastrointestinal tract, various batch and continuous luminal digestion models simulating enzymatic and microbial degradation were set up.…”
Section: Introductionmentioning
confidence: 99%